Age, Education Level, and Length of Service: A Triad of Factors Influencing the Performance of Community Health Workers in a Community-Based Stunting Prevention Program in Barito Kuala Regency - Raudatul Jannah; Deasy Arisanti; Syamsul Arifin; Yunita Sopiana; Budi Suryadi; Ahmad Yunani; Neka Erlyani (Media Publikasi Cendekia Indonesia, 2026)
Stunting remains a critical public health challenge in Indonesia. Posyandu cadres serve as frontline community health workers whose performance is vital for accelerating stunting reduction. This study aimed to evaluate the influence of age, educational level, and length of service on the performance of Posyandu cadres in Barito Kuala Regency. A quantitative cross-sectional study was conducted involving 377 Posyandu cadres selected through multistage random sampling. Data were collected using a structured Individual Work Performance Questionnaire (IWPQ). Data analysis included univariate, bivariate, and multivariate binary logistic regression to determine the predictors of cadre performance. The findings revealed that age and educational level significantly impacted cadre performance. Specifically, age was inversely associated with performance (p = 0.020; OR = 0.754), indicating that younger cadres outperformed their older counterparts. Furthermore, a higher educational level was positively correlated with high performance (p = 0.011; OR = 1.394). Conversely, length of service did not significantly influence performance outcomes (p = 0.387; OR = 1.290), suggesting that longer work experience does not necessarily equate to improved field efficacy. The performance of Posyandu cadres in community-based stunting prevention is driven by functional capacities linked to younger age and higher educational backgrounds, rather than accumulated years of service. Policymakers should prioritize educational qualifications and maintain an optimal age composition when designing capacity-building and recruitment strategies to optimize community health interventions.